[Cost-Effectiveness Analysis of TTFields with TMZ Versus TMZ in Monotherapy in Patients with Grade 4 Glioma in Italy] - Antonazzo, Ippazio Cosimo; Cortesi, Paolo Angelo; Silvani, Antonio; Ferrara, Pietro; Gribaudo, Giorgia; Losa, Lorenzo; Mantovani, Lorenzo Giovanni (Farmeconomia. Health Economics and Therapeutic Pathways, 2025)
INTRODUCTION: Grade 4 glioma is among the most aggressive forms of central nervous system tumors, posing a substantial clinical, humanistic, and economic burden on patients, caregivers, and society. Recent clinical and observational studies have demonstrated the efficacy and safety of Tumor Treating Fields (TTFields), in combination with temozolomide (TMZ), as a treatment option for patients with grade 4 glioma (TTFields-TMZ). However, this therapeutic strategy is not currently reimbursed in Italy. This treatment is currently reimbursed by the Regional Health Services/Health local authorities on a case-by-case basis, leading to inconsistent access nationwide. Therefore, the objective of this study was to assess the cost-effectiveness of TTFields-TMZ compared to TMZ monotherapy. METHODS: A partitioned survival model was developed from the perspective of the Italian National Healthcare Service (NHS), adopting a lifetime time horizon. The model estimated total costs, life years (LYs), quality-adjusted life years (QALYs), and the incremental cost-effectiveness ratio (ICER). Demographic and clinical characteristics of the simulated cohort were primarily derived from the pivotal EF-14 trial. Other model parameters (e.g., adverse event rates, survival probabilities, utility values) were obtained from the EF-14 trial and supplemented by literature review. Treatment costs, as well as those related to adverse event management and disease progression, were calculated based on Italian national and regional reimbursement tariffs. One-way sensitivity analysis and probabilistic sensitivity analysis (PSA) were performed to evaluate the impact of parameter uncertainty. RESULTS: TTFields-TMZ was associated with an overall cost of €186,386, compared to €40,743 for TMZ monotherapy. TTFields-TMZ yielded 3.82 LYs and 2.99 QALYs, whereas TMZ monotherapy yielded 2.12 LYs and 1.65 QALYs. This resulted in an ICER of €83,221 per LY gained and €109,026 per QALY gained. Sensitivity analyses confirmed the robustness of the base-case findings. CONCLUSIONS: The findings align with the QALY threshold typically applied by international Health Technology Assessment (HTA) bodies for rare disease treatment and offer robust evidence to inform healthcare decision-makers regarding the adoption of TTFields-TMZ for patients with grade 4 glioma, thereby supporting the efficient allocation of healthcare resources.